The influence of lithium oxybutirate on the rhythmic organization of daily dynamics of Na+, K+, Ca2+ and Li+ contents in blood, brain and urine of rats during summer solstice - T. A. Zamoshchina; Kh. M. Shraim; Ye. V. Ivanova (Бюллетень сибирской медицины)
Aimed at studying the influence of lithium oxybutirate on rhythmic organization of daily dynamics of Na+, K+, Ca2+ and Li+ contents in blood, brain and urine of rats during summer solstice, experiments on 84 male rats were performed. Cations’ content in blood, brain and urine of rats was determined on the flaming photometer of “Karl Zeiss” firm. Lithium oxybutirate slowed down rhythmic change of sodium level in blood and brain, potassium level in brain and lithium level in urine to endogenous mode. The drug promoted accumulation of sodium and lithium in brain tissue while preserving level of calcium and potassium unchanged; potassium was redistributed into peripheral tissues.